O PNLD Literário: o acesso ao livro no Brasil e a atuação dos editores de livros infantis e juvenis – discussões e perspectivas - Caille, Gilsandro Vieira Sales (2025)
This dissertation discusses the Brazilian public policy of access to literature books by schools: the PNLD literary program, its structural requirements and its scope, as well as the importance of literary language through the analysis of titles acquired by the program, in addition to the role of publishers in this process. This study seeks to answer a central problem question, which is to understand how the PNLD has contributed to building a reading society and how the work carried out by children's and young adult literature publishers relates to this. In view of the low levels of reading and access to literary language in Brazil, we will seek to debate the need for government investment in purchases of literature books, analyzing works acquired by the program at different times, as well as the official documents that establish the rules of participation of publishers (the so-called public notices). We will also try to reflect on how literary language (with a special focus on literature for young people) can contribute to improving reading rates in our country. In the midst of these analyses and reflections, we will always be grounded in theory that deals with the right to literature (Candido, 2004; LibrandiRocha, 2014), literature in the classroom (Dalvi, 2018; Todorov, 2020) and literature for young people (Antunes, 2019; Colomer, 2003; Zilberman, 2003), among other bibliographical sources that discuss the hypotheses of our research